2013
DOI: 10.12659/msm.889077
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of volume, position of stone, and hydronephrosis with microhematuria in patients with solitary urolithiasis

Abstract: BackgroundThe aim of this study was to determine the relationship between hematuria and volume, position of stone, and hydronephrosis in patients with a solitary stone, using unenhanced multidetector computed tomography (MDCT).Material/MethodsThis retrospective study evaluated the clinical and radiological records of 83 patients undergoing MDCT for the evaluation of acute flank pain and suspected renal colic, who also underwent a microscopic urinalysis at the emergency department of our hospital during a 1-yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 24 publications
(35 reference statements)
0
6
1
Order By: Relevance
“…Our sample size may have been too small to detect one, although previous studies have also failed to demonstrate a significant correlation between stone size and the presence of hematuria 10. We did find, however, a significant difference in the mean size of ureteral stones resulting in minimal-to-mild hydronephrosis (4.1mm) versus those resulting in moderate-to-severe hydronephrosis (6.9 mm, p < 0.0001).…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Our sample size may have been too small to detect one, although previous studies have also failed to demonstrate a significant correlation between stone size and the presence of hematuria 10. We did find, however, a significant difference in the mean size of ureteral stones resulting in minimal-to-mild hydronephrosis (4.1mm) versus those resulting in moderate-to-severe hydronephrosis (6.9 mm, p < 0.0001).…”
Section: Discussioncontrasting
confidence: 72%
“…One hypothesis is that larger ureteral stones may obstruct bleeding resulting in the absence of hematuria on UA; however, no studies have proven this. Additional factors that may influence or confound the presence or absence of microscopic hematuria on UA in patients with suspected urolithiasis include dehydration, females on their menstrual period, stone position,10 and the time interval between pain onset and urine collection 12. A recent study by Sahin et al examined the value of several parameters for predicting successful medical expulsion therapy in urolithiasis and found stone size, localization, degree of hydronephrosis, proximal ureteral diameter and ureteral wall thickness to be highly predictive, and patient age, BMI and stone density not predictive 13.…”
Section: Discussionmentioning
confidence: 99%
“…Within the selected articles, screening of the reference lists allowed to add 3 additional records. Finally, 49 studies [ 7 – 9 , 13 – 58 ] including 15′860 patients were identified as potentially relevant and were selected for the systematic review and meta-analysis. All of the included studies except two [ 30 , 50 ] were published in English.…”
Section: Resultsmentioning
confidence: 99%
“…As diagnostic tool the STONE Score was developed and validated; this score includes parameters as sex, duration of pain prior to presentation, race, nausea, vomiting and microhematuria [ 6 ]. Microhematuria prevalence in suspected renal colic has been studied in several trials, ranging from 55% [ 7 ] to 93% [ 8 , 9 ]. In order to better understand the difference existing in prevalence range, we performed a meta-analysis of studies dealing with microhematuria by suspected acute renal colic and/or confirmed urolithiasis.…”
Section: Introductionmentioning
confidence: 99%
“…The clear expression of VEGF in the mesangial region could promote the protein extravasation outside this region. Thus, increase in the vascular extracellular matrix would result in a subsequent increase in glomerular volume [ 21 ]. The repair of capillaries is necessary for glomerulonephritis healing [ 22 ], and VEGF is the essential factor that affects the growth and proliferation of glomeruli and peritubular endothelial cells.…”
Section: Discussionmentioning
confidence: 99%